OncomiR-181a promotes carcinogenesis by repressing the extracellular matrix proteoglycan decorin in hepatocellular carcinoma - Assal, Reem Amr; Abd El-bary, Rowan Bahaa El-din; Youness, Rana A.; Abdelrahman, Mohamed Mamdouh; Zahran, Hala; Hosny, Karim Adel; Esmat, Gamal; Breuhahn, Kai; El-Ekiaby, Nada; Fawzy, Injie Omar; Abdelaziz, Ahmed Ihab (BMC gastroenterology, 2024)
Proteoglycans are important tumor microenvironment extracellular matrix components. The regulation of key proteoglycans, such as decorin (DCN), by miRNAs has drawn attention since they have surfaced as novel therapeutic targets in cancer. Accordingly, this study aimed at identifying the impact of miR-181a in liver cancer and its regulatory role on the extracellular matrix proteoglycan, DCN, and hence on downstream oncogenes and tumor suppressor genes.
Gesehen am 17.06.2025